A novel salt inducible WRKY transcription factor gene, AhWRKY75, confers salt tolerance in transgenic peanut - Zhu, Hong (Plant physiology and biochemistry : PPB, 2021)
Copyright © 2021 Elsevier Masson SAS. All rights reserved.